Digital Marketing Communication to Enhance Cultural Soft Power in Gansu, China - Jing , Dang; Buranadechachai, Sukanya; Boonpiam, Sakdina (Journal of Dhamma for Life, 2025)
ABSTRACT This article mainly aims to 1) explore situation of the current digital marketing strategies employed for cultural promotion in Gansu 2) assess the existing level of Gansu's cultural soft power nationally 3) identify and analyze challenges hindering the effective use of digital marketing in Gansu's cultural promotion .The research methodology adopted for this study was a mixed methodology, combining both qualitative and quantitative research approaches. This hybrid approach can comprehensively and deeply study the role of digital marketing communication in enhancing the cultural soft power of Gansu Province. The research was carried out through three distinct processes: research proposal preparation, research procedures, and the final research report. The research findings revealed that: While Gansu's current digital marketing strategies have achieved some success, there remains significant room for improvement. Future strategies should place greater emphasis on the in-depth utilization of online platforms, the innovative dissemination of cultural and tourism content, and the expanded promotion of cultural products. These efforts aim to comprehensively enhance the province’s cultural soft power. Gansu's cultural soft power demonstrates certain advantages in traditional cultural domains such as natural landscapes and culinary heritage, where digital communication channels play a pivotal role in dissemination. However, the popularity and acceptance of cultural products remain relatively low, and public awareness of Gansu’s culture still needs to be improved. This analysis indicates that although Gansu has established a foundational level of cultural soft power, further optimization and expansion of cultural exchange in both depth and breadth are necessary to elevate its overall cultural influence. The aforementioned challenges and shortcomings suggest that Gansu has room to enhance its efforts in leveraging digital marketing communication to bolster cultural soft power. Addressing these challenges requires a broader integration of diverse communication channels, strengthening the market promotion of cultural products, and optimizing the content and formats of digital marketing. By doing so, Gansu can improve public awareness and recognition of its culture, effectively enhancing its cultural soft power and securing a more advantageous position in the global cultural landscape of the digital era.